Electronic Tuning in URu2Si2 Through Ru to Pt Chemical Substitution - Chappell, Greta L.; Nelson, William L.; Graf, D. E.; Baumbach, Ryan E. (Frontiers in Electronic Materials, 2022)
Studies that control the unit cell volume and electronic composition have been useful in revealing what factors lead to hidden order and superconductivity in the strongly correlated electron system URu$_2$Si$_2$. For example, isoelectronic tuning that increases the hybridization between the $f$ and conduction electron states (i.e., applied pressure and Ru $→$ Fe/Os chemical substitution) (i) converts hidden order into antiferromagnetism and (ii) destroys the superconductivity. The impact of nonisoelectronic chemical substitution has been less clear, but several unifying trends have recently emerged for chemical substitution vectors that qualitatively add electrons (e.g., Ru $→$ Rh/Ir and Si $→$ P). This includes (i) the rapid destruction of hidden order and superconductivity, (ii) composition regions where the underlying Kondo lattice is preserved but does not harbor an ordered state, and (iii) the emergence of complex magnetism at large substitutions. In order to assess the limits of this perspective, we have have investigated the series U(Ru$_{1-x}$Pt$_x$)$_2$Si$_2$ for $x$ $\lesssim$ 0.19, where the Ru and Pt $d$-shells differ substantially from each other. Magnetic susceptibility, electrical resistivity, and heat capacity measurements unexpectedly reveal a phase diagram with notable similarities to those of other electron doping series. This result reinforces the viewpoint that there is a quasi-universal affect that results from electron doping in this material, and we anticipate that an understanding of these trends will be useful to isolate what factors are foundational for hidden order and superconductivity.